Sistem Informasi Stok Seragam Berbasis Android sebagai Solusi Pengelolaan Persediaan Toko dengan Menggunakan Metode Prototype - Alda, Muhamad; Hanafi Harianja, Dio Arif; Putra Siregar, Armansyah; Septiawan, Muhammad Angga; Ramadhan, M. Rizky (Journal of Information System Research (JOSH), 2026)
Retail business management requires systems that are capable of providing accurate and timely information, particularly in managing inventory, such as in school uniform stores. Poor inventory monitoring may lead to various problems, including stock discrepancies, recording errors, and difficulties in obtaining up-to-date inventory information. At Toko Seragam Faiz, the management of uniform stock for elementary, junior high, and senior high schools is still performed manually, which has not yet supported efficient and accurate inventory control. Therefore, this study aims to design and develop an Android-based Uniform Stock Information System as a solution for inventory management at Toko Seragam Faiz. The system is designed to manage product and stock data in an integrated manner, enabling fast and accurate access to inventory information through mobile devices. The system development employs the prototyping method, which involves direct user participation during the design process to ensure that the developed system meets operational requirements. The results of this study are expected to assist store owners and staff in monitoring uniform stock more effectively, improving inventory management efficiency, and minimizing stock recording errors.